The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0734016814529965
|View full text |Cite
|
Sign up to set email alerts
|

Disciplinary Infractions Behind Bars

Abstract: Using data from one Midwestern state, this article investigates whether or not characteristics of importation and deprivation serve as predictors of receipt of institutional disciplinary infractions. The results of the logistic regression analyses indicate that both importation and deprivation factors were significant indicators of having received disciplinary infractions. Specifically, among 585 adult male inmates, data reveal that two importation measures and two deprivation measures were significant predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 71 publications
(158 reference statements)
0
13
0
1
Order By: Relevance
“…Beyond these issues related directly to inmates, correctional institutions largely devoid of inmate misconduct may also feature more efficient management. Staff members may be less burdened with detection, documentation, and resolution of inmate disciplinary infractions, which may allow them to become more productive by devoting more time to additional responsibilities (Tewksburry et al, 2014). This may contribute to reducing costs associated with employing large numbers of correctional officers and may offset the negative impact of high staff member turnover rates (Auty et al, 2017;Memory et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond these issues related directly to inmates, correctional institutions largely devoid of inmate misconduct may also feature more efficient management. Staff members may be less burdened with detection, documentation, and resolution of inmate disciplinary infractions, which may allow them to become more productive by devoting more time to additional responsibilities (Tewksburry et al, 2014). This may contribute to reducing costs associated with employing large numbers of correctional officers and may offset the negative impact of high staff member turnover rates (Auty et al, 2017;Memory et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Safer correctional institutions are also likely to be more attractive workplaces to both current and future prison employees (Marcum et al, 2014). Moreover, fewer incidents of inmate misconduct may lead to reduced costs associated with the negative repercussions of such behavior, such as inmate and staff member injury and destruction of prison property and infrastructure (Tewksburry et al, 2014). Finally, penitentiary treatment resort less to punitive strategies that a considerable amount of research has shown to be associated with increased recidivism (Andrews & Bonta, 2010a, 2010bBonta & Wormith, 2013;Bonta et al, 2011;McGuire, 2011McGuire, , 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not the focus of this particular study, another important domain widely known to influence rates of prison violence is the role of the situational and environmental factors, which almost surely constrains the rates of physical aggression behind bars (Gadon, Johnstone, & Cooke, 2006;Sorensen, Cunningham, Vigen, & Woods, 2011;Tewksbury, Connor, & Denney, 2014). Forensic practitioners working in this area might consider the PRISM model (promoting risk interventions by situational management; Cooke & Johnstone, 2010) as a means of moving beyond simple individual-level risk factors when they engage in the process of institutional risk assessment and management.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the determinants of prison misconduct have considered many theoretical formulations, most notably importation and deprivation models. The importation model holds that individuals bring their prior characteristics, values, and beliefs into prison, which in turn influence their adjustment/maladjustment to the prison setting (Berg & DeLisi, 2006;, while the deprivation model proposes that inmate maladjustment during incarceration is tied to the pains of imprisonment stemming from an unfavorable, severe, and brutal prison environment (Crewe, 2011;Morris, Longmire, Buffington-Vollum, & Vollum, 2010;Tewksbury, Connor, & Denney, 2014). However, as some advocates note, each model in seclusion may be insufficient in explaining prison misconduct (Steiner, Butler, & Ellison, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%